2005
DOI: 10.2739/kurumemedj.52.67
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors after Potentially Curative Resection in Stage II or III Colon Cancer

Abstract: It is important to identify factors that are predictive of outcome after a curative resection in colon cancer in order to optimize adjuvant therapy. To investigate these prognostic factors we conducted a retrospective analysis of our clinicopathological data. A total of 190 patients with a pathological stage II or III colon cancer underwent potentially curative resection with lymphadenectomy at our hospital between 1990 and 1998. These patients received no preoperative chemotherapy, immunotherapy or radiothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In many studies, metastasis to nearby lymph nodes is introduced as an independent variable associated with survival of patients (Berti et al, 1983;Park et al, 1999;OGATA et al, 2005). Also, in the current study, the variable relationship with survival time was significant in both univariate and multivariate analysis.…”
Section: Cox Vs Log-logistic Modeling In Crc Patientssupporting
confidence: 57%
“…In many studies, metastasis to nearby lymph nodes is introduced as an independent variable associated with survival of patients (Berti et al, 1983;Park et al, 1999;OGATA et al, 2005). Also, in the current study, the variable relationship with survival time was significant in both univariate and multivariate analysis.…”
Section: Cox Vs Log-logistic Modeling In Crc Patientssupporting
confidence: 57%
“…The postoperative pathological fi ndings in the eight stage II patients in our study showed positivity for moderate microscopic venous invasion, and microscopic venous invasion has been reported to be a highrisk factor in stage II patients. 11 No age limit was placed on those receiving the oral UFT plus LV regimen in the present study, but we chose not to administer oral UFT plus LV to patients with performance status 2 or more. Five elderly patients (75 years of age or older) were treated with oral UFT plus LV.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical therapy is the basis of treatment for patients with colon cancer, multimodal therapeutical concepts are currently applied not only in metastatic disease and Dukes C patients but also in Dukes B [ 18 - 20 ]. Further, the introduction of new drugs has extended the therapeutic options [ 21 , 22 ] and ongoing studies with novel targeted therapies will show their results in the next years.…”
Section: Discussionmentioning
confidence: 99%